Periodontal Disease: The Good, The Bad, and The Unknown - Sedghi, Lea M.; Bacino, Margot; Kapila, Yvonne Lorraine (Frontiers in Cellular and Infection Microbiology, 2021)
Abstract Periodontal disease is classically characterized by progressive destruction of the soft and hard tissues of the periodontal complex, mediated by an interplay between dysbiotic microbial communities and aberrant immune responses within gingival and periodontal tissues. Putative periodontal pathogens are enriched as the resident oral microbiota becomes dysbiotic and inflammatory responses evoke tissue destruction, thus inducing an unremitting positive feedback loop of proteolysis, inflammation, and enrichment for periodontal pathogens. Keystone microbial pathogens and sustained gingival inflammation are critical to periodontal disease progression. However, recent studies have revealed the importance of previously unidentified microorganisms, including various viruses, phages, and bacterial species, involved in disease progression. Moreover, newly identified immunological and genetic mechanisms, as well as environmental host factors, including diet and lifestyle, have been discerned in recent years as further contributary factors in periodontitis. These factors have collectively expanded the established narrative of periodontal disease progression. In line with this, new ideologies related to maintaining periodontal health and treating existing disease have been explored, such as the application of oral probiotics, to limit and attenuate disease progression. The role of systemic host pathologies, such as autoimmune disorders and diabetes, in periodontal disease pathogenesis has been well noted. Recent studies have additionally identified the reciprocated importance of periodontal disease in potentiating systemic disease states at distal sites, including Alzheimer’s disease, inflammatory bowel diseases, and oral cancer, further highlighting the importance of the oral cavity in systemic health. Here we review long-standing knowledge of periodontal disease progression while integrating novel research concepts that have broadened our understanding of periodontal health and disease in the field of periodontology. Further, we delve into innovative hypotheses in the field that may evolve to address significant gaps in the foundational knowledge of periodontal disease